TELENCEPHALON VASCULARITY IN COMMON FOX (Vulpes vulpes) - Benedykt Skoczylas; Witold Brudnicki; Krzysztof Kirkiłło-Stacewicz; Włodzimierz Nowicki; Jan Wach (Slovenian Veterinary Research, 2017)
The studies of the vascularization of the cerebrum in common fox were performed on 80 cerebral hemispheres. It was found that the middle cerebral artery is the strongest vessel supplying blood to the cerebrum. The artery gets divided into ten permanent branches. Two olfactory arteries supply the region of the cerebrum located on the border between the old and the new cortex. The other eight are divided into three branches heading towards the frontal lobe of the brain, two branches heading towards parietal lobe and three temporal branches heading towards the temporal part, that supply the region of the new cortex. The frontal, parietal and temporal branches descended independently from the main trunk of the middle cerebral artery or formed a common trunk. Common trunks for respective groups of branches have been described as the rostral, dorsal and caudal middle cerebral artery. In 7.5% of cases there were two independent branches of the middle cerebral artery extending from the rostral cerebral artery.